A Case of New-onset Autoimmune Type-1 Diabetes Mellitus Following COVID-19 Infection - Taşkaldıran, Işılay; Nar, Aslı (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Background: After COVID-19 infection, various mechanisms may initiate an increased risk of developing DM. This study presented a newly developed autoimmune Type 1 DM (T1DM) case in an adult patient after a SARS-CoV-2 infection. Case Presentation: A 48-year-old male patient presented with complaints of weight loss and blurred vision. His blood sugar and HbA1c were measured as 557 mg/dl and 12.6%, respectively. His medical records showed no known diagnosis of DM. He had a SARS-CoV-2 infection 4 weeks ago. Then, we diagnosed DM and started basal-bolus insulin therapy. C-peptides and autoantibodies were requested from the patient to explore the etiology of diabetes. Glutamic acid decarboxylase (GAD) antibody was > 2000 U/mL (ref: 0-10); therefore, the patient was accepted as having autoimmune T1DM. New-onset DM cases triggered by COVID-19 have increasingly been reported recently. SARS-CoV-2 virus, using the ACE2 receptor in the pancreas, can enter beta cells and causes damage to these islets and impaired insulin secretion, leading to acute diabetes mellitus. In addition, the abnormal immunity elicited by SARS-CoV-2 can also induce autoimmune destruction of pancreatic islet cells. Conclusion: T1DM may be an uncommon but possible complication due to the COVID-19 virus among genetically predisposed individuals. Overall, the case highlights the importance of preventive measures, such as vaccination, to protect against COVID-19 and its complications.
Keywords: glutamic acid decarboxylase